Effect of mycorrhization on the growth of plantain seedlings in substrate with and without the presence of plant parasitic nematodes (2011)
We compared the effect of pre-inoculation with the following arbuscular mycorrhizal fungi (AMF), on the growth of vegetative propagules (suckers) of plantain (Musa AAB): 1) Glomus fistulosum, 2) Glomus fasciculatum, and 3) commercial inoculum (mixture of G. aggregatum, G. fistulosum, G.manihotis, G. fasciculatum, Kuklosplora colombiana and Scutellospora spp.), compared with a control without AMF, in substrate with and without the presence of Radopholus similis and Helicotylenchus spp.. Furthermore, we evaluated the effect of AMF on the final amount of plant parasitic nematodes in roots and rhizosphere soil. The results indicated a significant intensification in the mycorrhizal colonization in roots inoculated with commercial inoculum of AMF (40 - 41%) compared with control and other AMFs (